Сучасний ринок біоактивних керамічних матеріалів і перспективи його розвитку - Дубок, В.А.; Лашнева, В.В.; Шинкарук, О.В.; Дубок, О.В. (Вісник Українського матеріалознавчого товариства, 2017)
A comparative analysis of the bioactive ceramic materials used in surgery to restore bone tissue and currently available on the market has been performed,. The properties of materials of different origin - biogenic, xenogenic and synthetic - are compared. The physicochemical and biological mechanisms of the interaction of these materials with the organism have been analyzed and it is convincingly shown that only synthetic biologically active ceramic materials can guarantee complete controlled restoration of bone tissue under controlled bioresorption, without the risks of infection, with zero load of the body's immune system, with the possibility to stimulate simultaneously the synthesis of useful enzymes and treatment of existing diseases, and also to be used as depot of scarce microelements in the body.